Sodium channel Nav1.8 immunoreactivity in painful human dental pulp - Tate S; Plumpton C; Yiangou Y; Renton T; Bountra C; Anand P (BMC, 2005)
Abstract Background The tetrodotoxin-resistant voltage-gated sodium channel Nav1.8 (SNS1/PN3) is expressed by nociceptors and may play a role in pain states. Methods Using specific antibodies for immunohistochemistry, we studied Nav1.8 - immunoreactivity in human dental pulp in relation to the neuronal marker neurofilament. Human tooth pulp was extracted from teeth harvested from a total of twenty-two patients (fourteen without dental pain, eight patients with dental pain). Results Fibres immunoreactive for Nav1.8, were significantly increased on image analysis in the painful group: median (range) Nav1.8 to Neurofilament % area ratio, non-painful 0.059 (0.006-0.24), painful 0.265 (0.13-0.5), P = 0.0019. Conclusion Nav1.8 sodium channels may thus represent a therapeutic target in trigeminal nerve pain states.